AN INVENTORY OF INDIGENOUS PLANTS USED AS ANTHELMINTICS IN AMATHOLE DISTRICT MUNICIPALITY OF THE EASTERN CAPE PROVINCE, SOUTH AFRICA - Wintola, Olubunmi Abosede; Afolayan, Anthony J. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Intestinal parasitic infections are among the most common chronic human infections in developing countries; particularly within the tropical and subtropical regions. An ethno-botanical survey was carried out to document medicinal plants used for the treatment of intestinal worms in Amathole District Municipality of the Eastern Cape Province (ECP), South Africa Materials and methods: A questionnaire-guided interview of the indigenous people by random sampling was done with the help of an interpreter during the survey of the district. Results: Medicinal plants mostly used for traditional management of intestinal worms were selected from 13 plant families: Alliaceae, Anacardiaceae, Asphodelaceae, Asteraceae, Crassulaceae, Dracaenaceae, Fabaceae, Hypoxidaceae, Lamiaceae, Longaniaceae, Punicaceae, Polygonaceae, and Verbenaceae. Out of these, Hypoxis hererocallidea (17%), Strychonos henningsii (14%), Rumex lanceolatus (12%), Ozoroa mucronata (9%) and Acacia karoo (9%) belonging to the families Hypoxidaceae, Longaniaceae, Polygonaceae, Anacardiaceae and Fabaceae respectively were found as the most cited, the least cited plant was Cotyledon orbiculata (2%). Leaves and roots from these plants were found to commonly used (36%), followed by the root (27%), bark (14%), the bulb and stem (9%), and rhizome collectively constitute (5%). Oral method administration by decoction (50%) and infusion (39%) was however found to be a common method by respondents. Conclusion: The current study however showed that ethno-pharmacological knowledge of the traditional healers in ECP largely depends on naturally growing species, documentation of which will go a long way in validating the therapeutic uses and safety of these plants as anthelmintic plants.